Assessment of community-driven drought risk management strategies in pastoral and agro-pastoral district of Bale zones south east Ethiopia - Abdela, Umer (Frontiers in Environmental Science, 2024)
Pastoral communities in Ethiopia's Bale Zone face a constant threat: drought. The Bale lowlands are particularly vulnerable due to unpredictable rainfall patterns. A four-year drought cycle had gripped the region, as reported by the pastoralists themselves. Rising temperatures and declining rainfall painted a concerning picture, leading to a cascade of problems: crop failures, food insecurity, outbreaks of diseases, and increased child school dropout rates. This in-depth study aimed to shed light on the impact of drought on these communities and their remarkable capacity to adapt. By bridging the knowledge gap on drought's influence and local coping mechanisms, the study hoped to inform future interventions. The objectives were to identify the impact of drought on Bale's pastoral communities and to identify the coping mechanisms employed by these communities. The study utilized a mixed-methods approach to capture both qualitative and quantitative data. Data collection techniques included: Engaging with knowledgeable community leaders provided valuable insights into historical trends, community perceptions, and local decision-making processes, Facilitating group discussions allowed community members to share their experiences, concerns, and coping mechanisms in a collaborative setting and administering standardized surveys to a representative sample of households allowed for the quantification of drought's impact and the prevalence of various adaptation strategies. The Results shows all study locations experienced drought for four consecutive years (100%), Pastoralists reported rising temperatures and declining rainfall. The drought resulted in, Crop failures, Food insecurity, Livestock deaths, increased human and livestock diseases increased child school dropout rates. The study concluded that despite the challenges, the study revealed a heartening story of resilience. Bale's pastoral communities haven't succumbed to despair. Instead, they have developed a multifaceted approach to cope with drought, including: Utilizing existing water sources and creating communal grazing areas for better water conservation, Splitting herds to reduce grazing pressure, implementing early morning grazing to capitalize on dew, diversifying livestock breeds, and strategically destocking herds before droughts to ensure long-term herd sustainability, Diversifying income through trade, transportation services, and petty trade to reduce dependence on livestock production during droughts.